Lexical Cohesion in Sunset Magazine's Articles - Wida Sarah Nur Azkia; Yessy Purnamasari (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2022)
Producing quality in writing is not easy to do. The selection of vocabulary in writing affects the quality of writing. There are still difficulties in writing, especially for students. The students lack an understanding of lexical cohesion. Regarding the problems identified, this research aims to find out the lexical cohesion used in magazine articles and to analyze the employment of lexical cohesion in magazine articles. This research uses a qualitative descriptive method to explain the lexical cohesion occurring in the magazine articles. In addition, this research uses Paltridge’s (2012) theory of lexical cohesion. After identifying and analyzing the data, it was found that all lexical cohesion types have occurred 307 times in the magazine articles: repetition, synonymy, antonymy, hyponymy, meronymy, and collocation. Synonymy is the most frequently used lexical cohesion type in the magazine articles, followed by collocation. The use of synonymy and collocation creates the cohesiveness of the text. The magazine articles become rich in vocabulary, not monotonous, and understandable to the readers. The results of this research show how article writers, which are the experts in writing published works for a large audience, make their writing cohesive.